2015
DOI: 10.1002/eji.201445289
|View full text |Cite
|
Sign up to set email alerts
|

HLA class I downregulation is associated with enhanced NK‐cell killing of melanoma cells with acquired drug resistance to BRAF inhibitors

Abstract: The frequent development of drug resistance to targeted therapies in cancer patients has stimulated interest in strategies counteracting resistance. Combining immunotherapies with targeted therapies is one such strategy. In this context, we asked whether human NK cells can target melanoma cells that have acquired resistance to selective inhibitors targeting activating mutants of the B‐Raf kinase (BRAF inhibitors, BRAFi). We generated drug‐resistant cell variants in vitro from human BRAF‐mutant melanoma cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 53 publications
(50 reference statements)
0
22
0
1
Order By: Relevance
“…This reprogramming of the immune microenvironment results in an increase in both MHC Class I-mediated antigen presentation and T cell infiltration (35,36), thus unleashing host-adaptive anti-cancer immunity. Furthermore, recent studies have shown that HLA class I downregulation is associated with enhanced NK-cell killing of melanoma cells with acquired drug resistance to BRAF inhibitors (37). In contrast, the MEK inhibitor trametinib alone or in combination with BRAF inhibitor dabrafenib suppressed T-lymphocyte proliferation, cytokine production, and antigen-specific expansion.…”
Section: Discussionmentioning
confidence: 99%
“…This reprogramming of the immune microenvironment results in an increase in both MHC Class I-mediated antigen presentation and T cell infiltration (35,36), thus unleashing host-adaptive anti-cancer immunity. Furthermore, recent studies have shown that HLA class I downregulation is associated with enhanced NK-cell killing of melanoma cells with acquired drug resistance to BRAF inhibitors (37). In contrast, the MEK inhibitor trametinib alone or in combination with BRAF inhibitor dabrafenib suppressed T-lymphocyte proliferation, cytokine production, and antigen-specific expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while GSEA indicated that immune pathways were the defining gene expression phenotype in PD-L1-positive tumors, there was also a novel immune gene signature associated with PD-L1-negative tumors and this signature may be an interesting basis for immunotherapy targets. Indeed, augmentation of NK cell activity through an anti-KIR antibody-based therapy is undergoing a phase-I clinical trial (ClinicalTrials.gov Identifier: NCT01714739) in combination with anti-PD-1 and anti-CTLA4 with goal of targeting MHC-Ideficient melanoma tumor cells (30,31). Nevertheless, many immune-related genes are driven by IFNg signaling and thus determining if any of these differentially expressed genes contribute to intrinsic immune evasion by melanoma cancer cells requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Combination treatment with BRAF inhibition and low-dose IL-2 led to improved BRAF efficacy with significantly lower burden of pulmonary metastases compared to monotherapy with either agent, providing support for combination trials of BRAF inhibition with NK stimulatory agents. Another study looking at the interaction between BRAF inhibition and NK cell function found that BRAF-resistant cell lines enhanced NK cell killing of melanoma cells [49]. MHC I was downregulated in BRAF-resistant cell lines, and this was associated with and at least partially contributed to the enhanced NK cell tumor killing.…”
Section: Key Concepts Underlying the Rationale For Combining Targetedmentioning
confidence: 99%